(untitled) (Research, Society and Development, 2020)
Objective: to evaluate the socio-educational actions of the “Friend of Diabetic Extension Project” (FDEP) and its repercussions for both patients and participating volunteers and employees. Methodology: Cross-sectional, quantitative and qualitative study. The sample consisted of 116 patients seen at the Casa do Diabético, 8 local employees and 53 FDEP volunteers. Data collection took place through interviews with patients, employees and volunteers. Results: When patients were asked about their satisfaction with the project, 62.07% reported feeling very satisfied and 36.20% said they were satisfied. Regarding the change in lifestyle, 50% of diabetics report that the project achieved a partial change in the style of their lives, 43.10% consider that the project helped a lot and was responsible for most of the changes. With regard to employees, 62.5% said they were very satisfied with the performance of the FDEP at home and 25% reported feeling satisfied. As for the academics participating in the project, 96.22% said they were satisfied with the FDEP and 94.34% said that the project allowed them to get closer to the community. Conclusion: FDEP enabled the dialogue between popular and academic knowledge, enabling the exchange of values ​​and experiences. It promoted improvements in the perception of diabetes mellitus not only for patients and their families, but also for NGO employees who were able to have more access to information and who in a way were able to pass on the information acquired.